Fermentation-Derived Bioactive Components from Seaweeds:Functional Properties and Potential Applications - Chye, Fook Yee; Pei, Wan Ooi; Seah, Young Ng; Mohd Rosni Sulaiman (2018)
Seaweeds are valuable sources of biologically active compounds that could be used as ingredients for pharmacological applications. Industrial fermentation using microorganisms provides a wide array of fermented foods and functional compounds with excellent health benefits. These fermentation-derived natural compounds have the potential to be applied as nutraceuticals and functional foods. Therefore, this paper presents an overview of the fermentation of sustainable seaweeds in producing valuable components, including anticoagulant, antioxidant, antimicrobial, anti-inflammatory, and anticancer. Fermentation-derived compounds are expected to receive more attention due to their environmentally friendly processing as well as consumer desire for natural foods.